Breaking the silence : restorative justice and child sexual abuse : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Policy at Massey University, Albany, New Zealand - Jülich, Shirley Jean (Massey University, 2001)
This research investigated the relationship between justice and child sexual abuse from the perspective of adult survivors. Utilising participant observation, unstructured interviews and focus groups within a feminist framework, 21 adult survivors of child sexual abuse (18 women and 3 men) were consulted to identify issues that were problematic for them. In addition, 2 jurors, 1 judge and 2 counsellors were interviewed. The findings indicated that child sexual abuse has been shrouded by a conspiracy of silence, caused partly by deeply entrenched structures within society. These forces combined with the complexity of recovery, including the possible impacts of Stockholm Syndrome, and the perceived inability of the criminal justice system to meet their needs, have appeared to silence many survivors of child sexual abuse. A review of the economic consequences and an analysis of the subsequent costs of child sexual abuse have indicated the need to implement programmes that would lessen the burden for victims, offenders, their families and the broader society. Survivors cautiously suggested that restorative justice might be sufficiently flexible to encourage victims of child sexual abuse to criminally report, thereby breaking the silence. A cost benefit analysis of a restorative justice programme indicated that significant savings could be made and highlighted that the prevention of child sexual abuse should be a priority. The findings of this research would have implications for policy makers and all those who provide services to victims and offenders of child sexual abuse. Stockholm Syndrome has highlighted the complexity of the recovery process for victims of child sexual abuse. This syndrome combined with the concerns of adult survivors of child sexual abuse would have implications for practitioners within the traditional criminal justice system and the restorative justice movement. Finally, the costs of child sexual abuse in New Zealand would have implications for justice agencies, health agencies, social welfare organisations and the Accident Compensation Corporation of New Zealand.
Keywords: Child sexual abuse; Adult child sexual abuse victims; Restorative justice; New Zealand; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360201 Public policy